2011
DOI: 10.1063/1.3562198
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of ordering transformation of a new Fe2(Mn,Cr)Si Heusler-alloy film by very high frequency plasma irradiation process during radio frequency sputter deposition

Abstract: A new Heusler alloy, Fe2(Mn,Cr)Si, that is likely to have high spin polarization (P) and high damping constant (α) was proposed to obtain high magneto-resistance ratio and low spin torque noise in a magnetic read head with a current-perpendicular-to-plane (CPP) giant magneto-resistance (GMR) multilayer. A very high frequency (VHF) plasma irradiation process during radio frequency (RF) sputter deposition was investigated to form the highly ordered structure of the Heusler alloy film with low thermal treatment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The film thicknesses and the deposition temperatures for the Ta seedlayer and Pt underlayer were optimized to obtain strong (111) orientation in the Pt underlayer 18) . Very-high-frequency (VHF) (40.68 MHz) plasma irradiation with an electric power of 5 W was applied during the radio-frequency (RF) (13.56 MHz) sputter deposition of the (Bi1-xBax)FeO3 film; VHF plasma irradiation with a low power density has previously been reported to accelerate the crystallization of the film 19) . The crystallographic orientations and the crystalline structures of the fabricated (Bi1-xBax)FeO3 films were analyzed by X-ray diffraction (XRD).…”
Section: Methodsmentioning
confidence: 99%
“…The film thicknesses and the deposition temperatures for the Ta seedlayer and Pt underlayer were optimized to obtain strong (111) orientation in the Pt underlayer 18) . Very-high-frequency (VHF) (40.68 MHz) plasma irradiation with an electric power of 5 W was applied during the radio-frequency (RF) (13.56 MHz) sputter deposition of the (Bi1-xBax)FeO3 film; VHF plasma irradiation with a low power density has previously been reported to accelerate the crystallization of the film 19) . The crystallographic orientations and the crystalline structures of the fabricated (Bi1-xBax)FeO3 films were analyzed by X-ray diffraction (XRD).…”
Section: Methodsmentioning
confidence: 99%
“…30) The VHF (40.68 MHz) plasma irradiation 28) during the reactive pulsed DC sputtering deposition of (Bi 1−x Ba x )FeO 3 films was performed with an electric power of 5 W to obtain the crystal grain growth of (Bi 1−x Ba x )FeO 3 thin films. The frequency of pulsed DC was varied from 50 to 250 kHz.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In a previous study, we fabricated Ta seedlayer=(111)-oriented Pt underlayer=(001)-oriented (Bi 1−x Ba x )FeO 3 multiferroic thin films with electric polarization perpendicular to the film plane onto a thermally oxidized Si wafer using an ultrahigh-vacuum (UHV) sputtering system. 27) Very high frequency (VHF) (40.68 MHz) plasma irradiation with an electric power of 5 W was applied during the radio-frequency (RF) (13.56 MHz) sputter deposition 28) of the (Bi 1−x Ba x )FeO 3 film. The (Bi 0.6 Ba 0.4 )FeO 3 film, in which the Ba concentration was optimized, exhibited hysteresis curves indicating ferromagnetic and ferroelectric behavior and had a saturation magnetization of about 60 emu=cm confirmed that the magnetization was reversed by applying only a local electric field.…”
Section: Introductionmentioning
confidence: 99%
“…The volume fraction (Vol.%) of MgO in the final film was adjusted by changing the numbers of MgO thin plates on the Fe50Pt50 target, the sputtering power, and/or the target-to-substrate (T-S) distance. During the sputtering, the VHF plasma irradiation 26) was fixed at 40.68 MHz with the electric power (PVHF) of 5 ~ 20 W as shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…The MgO 25) was used for isolation of FePt grains. The VHF plasma irradiation enhanced the L10 FePt phase during sputtering 26) . The new FePt•MgO MFM tip with very high coercivity was used for observation of AC magnetic image of perpendicular magnetic write head in this work.…”
Section: Introductionmentioning
confidence: 99%